Evaluation of Faculty Electronic Records Management at Universitas Gadjah Mada: Systems, Applications, and Repository Diversity - Maryatun, Isti; Riasmiati, Anna (Khazanah: Jurnal Pengembangan Kearsipan, 2025)
This study aims to evaluate electronic records management at Universitas Gadjah Mada (UGM) and identify the challenges and solutions faced by various faculties. The research method used is a comparative qualitative approach, collecting data through in-depth interviews and document analysis from several faculties with different electronic records management systems. The study results show that electronic records management at UGM varies across faculties. Some faculties, such as the Faculty of Cultural Sciences and Animal Science, still rely on manual methods or limited applications. In contrast, others, such as the Faculty of Pharmacy, Economics and Business, and Agricultural Technology, have started to develop more organized technology-based systems. The main challenges include limited human resources, data security risks, and suboptimal system integration. This study recommends creating a more integrated electronic records management system across all faculties, continuous training for records management staff, and measures to enhance data protection and secure the destruction of records. Implementing these recommendations will improve the efficiency, security, and effectiveness of electronic records management at UGM and serve as a reference for other faculties looking to optimize their electronic records management systems.